2011
DOI: 10.1186/1472-6874-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to knowledge and perception of women about smoking: a cross sectional study from a developing country

Abstract: BackgroundSmoking rates among women are currently low, but they are the fastest growing segment of cigarette smoking population in developing countries. We aimed to assess the knowledge and perceptions towards smoking and to identify the factors related with level of knowledge and perceptions among adult women in urban slums.MethodsThis was a cross sectional study conducted on 250 adult (≥18 years of age) women attending primary care clinics in three slums of Karachi, Pakistan. A pre-tested and structured, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
3
20
3
2
Order By: Relevance
“…[19] However, their knowledge of specific harmful effects of active smoking and exposure to ETS on the mother and fetus's health, such as prematurity, congenital anomalies and LBW, was less (1-7%) compared to our results (14-30%). A possible explanation of these differences in knowledge is the relatively high level of education in our study sample (51.7%).…”
Section: Discussioncontrasting
confidence: 86%
“…[19] However, their knowledge of specific harmful effects of active smoking and exposure to ETS on the mother and fetus's health, such as prematurity, congenital anomalies and LBW, was less (1-7%) compared to our results (14-30%). A possible explanation of these differences in knowledge is the relatively high level of education in our study sample (51.7%).…”
Section: Discussioncontrasting
confidence: 86%
“…The study did not measure cotinine level in the pregnant women blood, to see if they were telling the truth about their exposure to SHS. Another limitation was we did not specify whether the participants lived in rural or urban areas, as differences in the cultures and the socioeconomic characteristics have been confirmed in the literature (8)(9)(10). Also we did not assess the knowledge, attitude and behavior of the participants toward SHS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…One study in China found that over two-thirds of female smokers thought that ‘light’ or low tar cigarettes were less harmful than regular cigarettes,96 while another Chinese study found that awareness of ‘cigarettes made for women’ (women's brands) and believing that they were less harmful to health predicted smoking experimentation in female students 97. With regards to smoking during pregnancy, a study in Pakistan found that only 7% of women knew that smoking could lead to low birth weight; only one third of women knew that smoking caused lung disease 98. Similarly, a study in Zambia and the Democratic Republic of Congo found that pregnant women's knowledge of the health risks of smoking and SHS exposure was very limited 99.…”
Section: The Impact Of Tobacco Control Policies On Women and Girlsmentioning
confidence: 99%